A Reversibly Responsive Fluorochromic Hydrogel Based on Lanthanide–Mannose Complex. Issue 10 (13th March 2019) - Meng, Ke; Yao, Chi; Ma, Qianmin; Xue, Zhaohui; Du, Yaping; Liu, Wenguang; Yang, Dayong
Abstract: Fluorochromic materials that are dynamic in response to external stimuli are of great interest for the development of advanced sensors and luminescent materials. Herein, a design based on a lanthanide‐containing polymeric hydrogel possessing characteristic emission of lanthanides (Eu and Tb) and showing response to stimuli of metal ions is reported. The fluorochromic hydrogel is prepared using a lanthanide–mannose complex in gelation matrix. The lanthanide–mannose complex shows tunable fluorescent emission in response to Fe 2+, due to the inhibition of the "antenna effect" between metal ions and ligands upon stimulation. The fluorescent hydrogel shows reversible "On/Off" fluorochromic response to Fe 2+ /ethylenediaminetetraacetic acid (EDTA). Remarkably, the fluorescent hydrogel is proven nontoxic and biocompatible; and a proof‐of‐application as in situ 3D cell culture extracellular matrix with reversible fluorochromic "On/Off" switch upon Fe 2+ /EDTA is demonstrated. This reversibly responsive fluorochromic hydrogel demonstrates a way to fabricate smart optical materials, particularly for biological‐related applications where reversible response is required. Abstract : A fluorochromic hydrogel based on lanthanide complexes is reported. The hydrogel shows reversible fluorochromic response upon stimulation, due to the inhibition and recovery of the "antenna effect" between metal ions and ligands. The hydrogel is nontoxic and biocompatible, and is demonstrated by proof‐of‐application for 3D cell culture with a fluorochromic "On/Off" switch.